국제영화제와 <기생충>의 문화정치적 함의 - 백태현; Baek Tae-hyun; 주지영; Joo Ji-young (인문학연구, 2025)
본 논문은 봉준호의 영화 <기생충>(2019)이 국제영화제 수상과 글로벌 수용을 통해 정전으로 수용되는 과정을 구조적으로 분석한다. <기생충>은 한국의 상황과 공간을 보편적인 영화적 방식으로 양식화하는 것으로 계급 불평등이라는 전지구적 문제와 접속하였다. <기생충>을 향한 찬사는 봉준호 감독 개인의 성취와 한류의 영향에 의한 것이라기보다는 국제영화제가 주도한 영화 산업의 제도와 담론이 승인할 만한 이미지를 정교하게 배치한 결과로 봐야 한다. 국제영화제는 봉준호를 상업성과 정치성을 결합한 작가로 승인하는 전략을 통해, 봉준호라는 감독을 하나의 브랜드처럼 작동하게 만들어 그가 영화 외부의 담론 구조에 능동적으로 개입하는 해석 주체로 기능하게 만들어 주었다. 그는 글로벌 자본과의 협업 속에서도 사회적 문제의식을 지속적으로 표명하는 것으로 글로벌 영화 담론이 선호하는 정치적 미학의 절충선을 수행해 왔다. <기생충>은 이러한 상업적 작가주의의 정점에서 생산된 텍스트로 서구가 요구하는 타자로서 비서구권의 이미지를 구축하였다. 본 논문은 <기생충>이 단지 미학적 완성도로 설명될 수 없는 작품이며, 국제영화제의 승인 구조 속에 위치한 결과임을 비판적으로 분석한다. 이때 승인 구조는 외부로부터 부과되는 일방적 조건이 아니라, 비서구권 내부에서 자발적으로 구성되고 수행되는 것이기도 하다. <기생충>은 상업적 작가주의의 전략과 타자로서 자기 이미지의 적극적 수행을 통해 서구의 시선에 편입되었으며, 이를 통해 세계영화로 구성될 수 있었다. 이 연구는 트랜스내셔널 시네마의 담론 틀에서 비서구 영화가 세계영화로 승인되기 위해 만족시켜야 할 조건과 작동 방식을 비판적으로 고찰한다. This study offers a structural analysis of how Bong Joon-ho’s Parasite was canonized through international film festival accolades and global reception. The film connects to the global discourse on class inequality by stylistically encoding Korea’s socio-spatial context into a film style that conforms to universal codes. The acclaim surrounding Parasite should not be seen merely as the result of Bong’s artistic accomplishment or the Hallyu’s global influence, but rather as an outcome of institutional mechanisms that authorize images deemed suitable for approval. International film festivals strategically positioned Bong as an auteur who merges political critique with commercial appeal, turning his name into a cultural brand capable of intervening in the global discursive field. Through his ongoing engagement with global capital and socially grounded storytelling, Bong performed a calibrated aesthetic-political balance favored by global film discourse. Parasite, emerging at the apex of this branded authorship, constructs a legible image of the non-Western Other for Western spectatorship. This paper argues that Parasite cannot be explained solely by its aesthetic achievement, but must be understood as a product of its embeddedness within the festival approval structure. This structure is not merely imposed from the outside but is also voluntarily performed and internalized within non-Western cultural production. Through strategic self-othering and affective alignment, Parasite secured its place in world cinema. This study critically interrogates the affective, ethical, and discursive conditions that non-Western films must fulfill for transnational recognition.